Peranan Kepemimpinan Dalam Meningkatkan Disiplin Kinerja Pegawai Fraksi DPRD Provinsi Sumatera Utara Melalui Fungsi Pengawasan - Rahmawani Afwika; Laylan Syafina (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to determine the role of leaders in efforts to improve employee work discipline through the role of supervisory functions. This research also examines the obstacles that hinder leadership from improving employee work discipline. This research uses a qualitative approach and is included in the qualitative descriptive research category. The data used was obtained from interviews with Gerindra Faction employees. Research shows that the Gerindra Faction is carrying out its duties well as leaders. However, faction employees continue to report to the office not on time, thereby disrupting employee discipline. In the Gerindra Fraction Office, the role of leadership is very important because it helps optimize work efficiency and effectiveness. Furthermore, leaders can reduce the level of employee indiscipline by providing punitive sanctions.